Severe Complications of Diabetes - Yuldosheva Roila Jumayevna (Zien Journals, 2022)
Diabetes mellitus is a chronic metabolic disease that is characterized by an increase in blood glucose levels due to deficiencies in insulin exposure, insulin secretion, or both. Effective treatment of diabetes is critical, otherwise chronic uncontrolled diabetes can lead to late complications of diabetes, particularly neuropathy, retinopathy, cardiomyopathy, and nephropathy. Researches have shown that diabetes mellitus is one of the leading causes of risks worldwide.
Keywords: diabetes; glucose; insulin; obesity